Morphological response of the ‘Barraganete’ plantain (Musa AAB) to magnesium levels under dryland conditions - Cedeño-Zambrano, José; Cobeña-Loor, Nexar; Jiménez-Flores, Luis; Ulloa, Santiago; López-Mejía, Francel; Sánchez-Urdaneta, Adriana (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Platain (Musa AAB) is a crop of great economic importance in Ecuador due to its extensive planting area, high production, and job creation. Considering its high nutrient requirement, this research was conducted to evaluate the response of morphological variables in 'Barraganete' banana (Musa AAB) to the application of different levels of magnesium. An experiment was carried out in 'El Carmen' canton, province of Manabí, Ecuador (-0,259503 S, -79,427558 W), which included six levels of Mg application (0, 25, 50, 75, 100, and 125 kg.ha-1), under a randomized complete block design with three replications. The variables evaluated (plant height, pseudostem circumference, leaf length and width, leaf area, and total leaves) were subjected to repeated measures analysis over time, with weekly measurements. Statistical analyses showed that the morphological variables evaluated did not present significant differences between Mg doses; however, the temporal analysis highlighted that the highest doses promoted greater growth of vegetative organs. Overall, the results suggest that Mg application at doses equal to or greater than 50 kg.ha⁻¹ could be considered. This finding supports the need for future studies to compare morphological variables with yield, as well as evaluate profitability, to provide useful information for improving crop production under the study conditions.